(3fHPI ef CMhGd YHGS Bd cGTa GdZWGAs - (3GdfLaj, GHf cGTa GdZWGA, , Ydj Hf eMeO QVG Hf ehSi Hf LYaQ cGTa GdZWGA, J (B1350 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3adeG Kde GdESdGe KdeJg GdJj df JSO Ydi JYGbH GdCRefI hhbYJ GdhGbYI GdJj CfGN cdcgG HGdBjI GdHjfI agOJ Qcf GdTQjYI GdQcjf (B...s
(3BNQgG (B:s
... (3hHbjJ dg eQGKj CNQ de fKHJgG hjcaj ef GdbdGOI efgG GMGW HGdLjO hfMf fCed ef aVd Gddg Ld LdGdg Cf jLGRj gDdGA GdUahI HGdEMSGf hGdJaVd (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs